The answer to your question is A
For the given trinomial
![a=-1, b=1 ,c=42](https://tex.z-dn.net/?f=a%3D-1%2C%20b%3D1%20%2Cc%3D42)
We need to multiply a by c
![-1 \times 42 = - 42](https://tex.z-dn.net/?f=%20-1%20%5Ctimes%2042%20%3D%20-%2042)
We split the middle term with these two factors
![7,-6](https://tex.z-dn.net/?f=%207%2C-6)
To obtain,
![- {x}^{2} + 7x -6x + 42](https://tex.z-dn.net/?f=%20-%20%7Bx%7D%5E%7B2%7D%20%2B%207x%20-6x%20%2B%2042)
We now factor
![- {x}^{2} + x + 42 \: = x( - x + 7) + 6( - x + 7)](https://tex.z-dn.net/?f=%20-%20%7Bx%7D%5E%7B2%7D%20%2B%20x%20%2B%2042%20%5C%3A%20%3D%20x%28%20-%20x%20%2B%207%29%20%2B%206%28%20-%20x%20%2B%207%29)
This implies
Answer:
The value of AM = 43
Step-by-step explanation:
As point M is the midpoint of AB, so
Given
AB = 8x - 50
AM = 2x + 9
so substituting AB = 8x - 50 and AM = 2x + 9 in the equation AB = AM + BM
AB = AM + BM
8x - 50 = 2x + 9 + BM
8x - 2x - 50 - 9 = BM
6x - 50 = BM
Thus,
BM = 6x - 59
As
AM = BM
so substituting AM = 2x + 9 and BM = 6x - 59 in the equation AM = BM
2x + 9 = 6x - 59
switch sides
6x - 59 = 2x + 9
subtract 2x from both sides
6x - 2x - 59 = 2x + 9 - 2x
4x - 59 = 9
add 59 to both sides
4x - 59 + 59 = 9 + 59
4x = 68
divide both sides by 4
4x/4 = 68/4
x = 17
Thus, the value of x = 17
Therefore, the value of AM will be:
AM = 2x + 9 = 2(17) + 9 = 34 + 9 = 43
Hence, the value of AM = 43
<u>Verification:</u>
AM = BM
2x + 9 = 6x - 59
2(17) + 9 = 6(17) - 59
34 + 9 = 102 - 59
43 = 43
and
AB = 8x - 50 = 8(17) - 50 = 86
Answer:
y=6+x
Step-by-step explanation:
2+6=8 6+6=12
Answer:
Step-by-step explanation:
8 ft = (12 * 8) = 96 inches
3 ft 9 in = (12 * 3) + 9 = 45 inches
510 gallons to 96 inches = x gallons to 45 inches
510 / 96 = x / 45....cross multiply because this is a proportion
(96)(x) = (510)(45)
96x = 22950
x = 22950 / 96
x = 239.0625 rounds to 239.1 gallons <===